Pengaruh penambahan fly ash variasi 0%, 5%, 10%, 15%, dan 20% terhadap kuat tekan beton - Tri Ari Wibawa (Jurusan T. Sipil Fakultas Teknik UMY, 2014)
Pengaruh penambahan fly ash variasi 0%, 5%, 10%, 15%, dan 20% terhadap kuat tekan beton